IMPLEMENTASI PENDIDIKAN KARAKTER - Oji Fahroji (QATHRUNÂ, 2020)
This study aims to: (1) describe the value of integrated character education at SMP Islam Al-Azhar 11 Serang City and SMP IT Rahaudatul Jannah Cilegon (2) describe the implementation of character education (3) reveal the results of the implementation of character education.This type of research is descriptive qualitative with normative, pedagogical, and psychological theological approaches. In connection with the data sources in this study are two data sources, primary data namely the principal, vice principal, teachers, and students and school members, while secondary data is a document on the condition of teachers, school facilities, profiles and lesson plans related to the object researched. The data is obtained through observation, interviews and documentation. The results showed that the value of character education that is integrated in the learning process is religious, disciplined, diligent, curiosity, caring, and responsibility. Meanwhile, the implementation of character education values ​​is also obtained through extracurricular activities which are carried out through dance, sports, religious, vocal and scientific works of youth, as well as the clean culture instilled in the two schools. The findings obtained were that imposing sanctions on students would explicitly provide a deterrent effect and this became respected by students, not to do it again.